The effects of neck and trunk stabilization exercises on upper limb and visuoperceptual function in children with cerebral palsy - Shin, Ji-Won (J Phys Ther Sci, 2016)
[Purpose] The present study aimed to investigate the effects of neck and trunk stabilization exercises on upper limb and visuoperceptual function in children with cerebral palsy. The Jebson-Taylor hand function test and the Korean Developmental Test of Visual Perception-2 (K-DTVP-2) test were utilised. [Subjects and Methods] The study subjects were 11 schoolchildren who had paraplegia caused by premature birth, and who had been diagnosed with periventricular leukomalacia. Kinesitherapy was implemented in individual children for eight weeks, twice a week, for 45 minutes at a time. After a preliminary evaluation, kinesitherapy, including neck and trunk stabilization exercises common to all the children, was implemented for eight weeks according to the functioning and level of each child. A post evaluation was performed after the eight weeks of kinesitherapy. [Results] The intervention showed a significant effect in five subcategories of the Jebson-Taylor hand function test, as well as according to the K-DTVP-2 test. [Conclusion] Because neck and trunk stabilization exercises requiring positive participation by the children included fundamental elements of daily living motion, the exercises might have had a positive effect on upper limb and visuoperceptual function.